Tectonic Consequences of a Uniformly Hot Backarc and Why is the Cordilleran Mountain Belt High? - Hyndman, R. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2015)
Why is the North American Cordilleran mountain belt high? We expect a thick crust to support high elevations by isostasy but, remarkably, the Cordilleran crust is thin. There is no crustal root. An important recent recognition is that the high elevation is supported by thermal expansion rather than by thickened crust. The elevation of the Cordillera is only one consequence of the Cordillera being uniformly hot and having a thin lithosphere, in common with most current or recent backarcs. Some other consequences of the high temperatures compared to the adjacent cool craton include: (1) The Cordillera and other backarcs are hot, weak mobile belts that can be deformed by available plate-tectonic forces, in contrast to stable cratons that cannot; (2) Most continental seismicity is concentrated in backarcs; (3) In the Cordillera there is widespread sporadic ‘backarc’ volcanism; (4) The high temperatures result in very low strength in the lower crust that allows lower-crust detachment; (5) The lower crust weakness facilitates large-scale crustal oroclines that may be independent of the upper mantle; (6) The lower crust in the Cordillera and other backarcs is in amphibolite- to granulite-facies conditions, ~800–900°C at the Moho; (7) In ancient backarcs globally, regional Barrovian metamorphism is concluded to be the result of high temperatures that predate the orogenic collision and deformation. No “heat of orogeny” is required. Following the termination of subduction, backarcs cool with a time constant of 300–500 m.y.